Innovating a constructivist learning model to instill cultural diversity respect into youths in a Thai tourism community - Srisawad, Paranee; Ounvichit, Tassanee (Kasetsart Journal of Social Sciences, 2016)
Local cultures are social tools to facilitate harmonious existence of man and environment. But today globalization process intensely reduced cultural diversity and would impact on harmonious man-environment co-existence. This study was based on an instrument case of the Kudijeen multicultural tourism community where local residents possessed diverse ethnicities, religions and ways of life and offered their sundry cultures as tourist attractions. This community possessed high risks of cultural losses and clashes due to internal diversity as well as arrivals of external cultures brought by visiting tourists and its context was favorable for devising a learning tool to reduce the risks. The study was aimed at assessing the cultural diversity respect of youths in the community and innovating and evaluating a learning process to elevate their respect. The study used the qualitative approach in collecting data relating to the historical, demographical and cultural background of the studied community and using the action research process, particularly the after-action reflection, to innovate a model for learning of cultural diversity respect through a joint effort of 15 voluntary youths and 22 community experts. The results of the study revealed that, prior to their participation in the study, the youths had low level of cultural diversity respect. In nine months of their learning action, the youths cultivated their respect to the level that they pre-determined. From their learning action, a constructivist learning model was innovated. In the L-CULTURA or the Learn-to- Cultivate Cultures Model, the youths engaged in nine spiraling steps of taking up challenges, checking stocks, planning self-study, searching for new information, sorting the information, conveying the information, getting feedbacks, reflecting on learning experience and creating habits. Community experts and the researchers played roles in scaffolding their learning process as motivators, stimulators, challengers, advisors, resource persons and facilitators.